Corrupt elites, administrative cadres and public service in Africa: Islands of vanity - Peter Adoko Obicci (Journal of Management and Science, 2025)
Undermining growth and governance in Africa are persistent corruption issues and inefficient public service delivery. It is still unclear how corrupt elites, administrative cadres, and public service are intricately related, despite a wealth of studies. This study investigates the relationships that corrupt elites, administrative cadres and public service delivery have in Africa, focusing on how these “islands of vanity” obstruct efficient government and progress. The elite theory is adopted by the paper to accomplish the latter purpose. The study employed a qualitative methodology and uses secondary data and examined previously published books, articles, reports and papers to find themes and patterns. The study demonstrates how the provision of public services is jeopardized by corrupt elites and administrative cadres who participate in rent-seeking activities, patronage networks, and bureaucratic corruption. These "islands of vanity" impede growth, erode institutions, and maintain inequality. To avoid repeating the mistakes and inefficiencies of the past, the paper suggests public service delivery changes that encourage the hiring and deployment of moral leaders and administrative cadres to make effective and efficient use of both current and projected public resources meant for effective service delivery. By highlighting the vital role of moral elites and administrative cadres and the requirement for contextualized solutions, this research advances knowledge of corruption and governance in Africa. Future studies should examine how global governance frameworks and outside actors affect Africa's efforts to combat corruption and enhance the provision of public services amid questionable practices of dishonest administrative cadres and elites.